Republic of Madagascar : Technical Assistance Report-Report on Technical Assistance Mission in External Sector Statistics (July 2-13, 2018). (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance report highlights that the mission visited Madagascar to aid in the external sector statistics (ESS), including the balance of payments and international investment position (IIP). The mission focused on assisting improving the coverage of IIP by better using the administrative sources or by identifying new data sources for private sector. A more sustained effort must be applied to the collection system to ensure the timelier submission of data of adequate quality. The compilation of the quarterly ESS, which is one of the main ESS objectives, requires both an increase in the number of compilers and a change of approach in the collection of source data. The quarterly data are compiled on the basis of the ESRI and should be supplemented by the collection of quarterly data using a simple survey of major public and private enterprises. The mission recommended a detailed one-year action plan with a set of priority recommendations carrying particular weight to make headway in improving the ESS.